The nurturing of creativity in the History classroom through teaching methods – the views of teachers and learners (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Nurturing creative thinking abilities in all learning areas and subjects is one of the cornerstones and ideals of Outcomes-Based Education (OBE) in South Africa. This article reports on the results obtained with a pilot study that set out to determine the extent to which creativity is presently nurtured in the History classroom. A qualitative study by means of semi-structured, oneon-one interviews with learners (n = 4) and teachers (n = 2) of History at a secondary school was conducted to determine learner and teacher perceptions related to the nurturing of creativity through the instructional practices of teachers applied during teaching and learning. The results revealed that the nurturing of creativity has not yet become reality in the History classroom. It was disconcerting to note that direct instruction dominates the teaching and learning of History and that very little opportunity for practical experience and interaction during teaching and learning exists. The article concludes with recommendations to teachers on how to purposefully enhance creativity during the teaching of History. This pilot study was conducted as partial fulfillment of the requirements for a BEd Honours degree, and to set the scene for a more extended study on creative thinking in History with larger groups of learners and teachers.
Keywords: creativity; creative thinking; lateral thinking; creativity and classroom practice; creativity and History teaching